Drop-Safe 360 - John, Elton; Mahdzir, Mubarak; Maul, Faustine Harry; Adam, Mohammed Afiq; Zerlin, Zendezion; Muspah, Nurul Faten Nazwatul Edora (2016)
Nowadays, the number of population in Sabah rapidly increase based on statistic that released by Malaysian Government. Since the population increased, the rate of accidents was unconditionally increased. The statistic of the accidents shows that accident occurs major cause by attitude of the driver personally, based on Jabatan Pengangkutan Jalanraya (JPJ) dan Polis Trafik DiRaja Malaysia. So, we ZEAFFA Tech. Sdn. Bhd. were motivated to introduce our product that will decrease the number of accident - which is called by 'Drop Safe 360'. This product was innovated by our CEO Company, Elton John. Literally this product was simply invented by Marc Newburger and Jeffrey Simon in United States but only with a certain feature. So, we take some of this idea to create with better innovation that can give many advantages to our customer. We think this product will be the most' useful innovator to the people in the future because of its unique feature at the same times its very simplest inventions.